The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1530/joe-16-0033
|View full text |Cite
|
Sign up to set email alerts
|

Folliculostellate cell interacts with pericyte via TGFβ2 in rat anterior pituitary

Abstract: The anterior pituitary gland comprises five types of endocrine cells plus non-endocrine cells including folliculostellate cells, endothelial cells, and capillary mural cells (pericytes). In addition to being controlled by the hypothalamic-pituitary-target organ axis, the functions of these cells are likely regulated by local cell and extracellular matrix (ECM) interactions. However, these complex interactions are not fully understood. We investigated folliculostellate cell-mediated cell-to-cell interaction. Us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 40 publications
1
14
0
Order By: Relevance
“…1c). As was the case in our previous report [28], TGFβ receptor II mRNA was detected in parenchymal cells, perivascular cells, and endothelial cells. Double staining showed that parenchymal cells were co-stained with S100 protein and that perivascular cells were co-stained with desmin (Fig.…”
Section: Discussionsupporting
confidence: 83%
See 3 more Smart Citations
“…1c). As was the case in our previous report [28], TGFβ receptor II mRNA was detected in parenchymal cells, perivascular cells, and endothelial cells. Double staining showed that parenchymal cells were co-stained with S100 protein and that perivascular cells were co-stained with desmin (Fig.…”
Section: Discussionsupporting
confidence: 83%
“…It is a potent regulator of ECM synthesis, in which signaling stimulates synthesis of ECM components [20, 28, 29]. Indeed, our past and present findings show that TGFβ2 induced fibromodulin and collagen synthesis in pericytes [28].…”
Section: Discussionmentioning
confidence: 79%
See 2 more Smart Citations
“…Quantitative real-time PCR and RT-PCR was performed as described in our previous report [8,13]. The primers used to amplify cDNA fragments were listed in Table 1.…”
Section: Real-time Pcr and Reverse Transcription (Rt)-pcrmentioning
confidence: 99%